2017
DOI: 10.1177/0145721717729806
|View full text |Cite
|
Sign up to set email alerts
|

Thinking About Cognitive Function: Perceptions of Cognitive Changes in People With Type 2 Diabetes

Abstract: Purpose The purpose of this study is 2-fold: (1) to explore how people with diabetes view diabetes-related cognitive problems and (2) to examine participants' ideas on a cognitive rehabilitation intervention to adapt it for persons diagnosed with type 2 diabetes (T2DM). Methods A qualitative descriptive study based on narrative interviews was conducted with adults (n = 10) with T2DM. The interview data were analyzed using content analysis. Results The interviews reflected 4 major themes: search for advice rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 30 publications
(42 reference statements)
2
34
0
3
Order By: Relevance
“…Participants often described not meeting the self-management standards that were set for them (by themselves or by their health-care provider) and felt that anything they could do to improve cognitive function would also help with diabetes self-management. The relationship of perceived cognitive function and diabetes self-management has been seen in the recent literature [13, 25] and suggests perceived executive function and memory capabilities are significantly associated with diabetes self-management adherence. Other studies have also found that self-management and glycemic outcomes are even worse when screening for cognitive dysfunction is delayed despite complaints of cognitive problems [26].…”
Section: Discussionmentioning
confidence: 99%
“…Participants often described not meeting the self-management standards that were set for them (by themselves or by their health-care provider) and felt that anything they could do to improve cognitive function would also help with diabetes self-management. The relationship of perceived cognitive function and diabetes self-management has been seen in the recent literature [13, 25] and suggests perceived executive function and memory capabilities are significantly associated with diabetes self-management adherence. Other studies have also found that self-management and glycemic outcomes are even worse when screening for cognitive dysfunction is delayed despite complaints of cognitive problems [26].…”
Section: Discussionmentioning
confidence: 99%
“…8,13 Perceived barriers alter rates of self-care and daily self-foot examinations. 13,[21][22][23] Decreased rates of self-foot examinations were associated with patient beliefs that foot examinations take too much time, are too much trouble, and are not important. 21,23 Patients who reported higher rates of daily self-foot examinations perceived fewer barriers.…”
mentioning
confidence: 99%
“…21,23 Self-efficacy and awareness of a neuropathy diagnosis are associated with higher rates of daily self-foot examinations. 21,22 The purpose of this project was to provide interactive self-foot examination education in an outpatient office setting and assess whether rates of daily self-foot examinations were affected. Perceived barriers to self-foot examinations were also assessed.…”
mentioning
confidence: 99%
See 2 more Smart Citations